2014
DOI: 10.3390/plants3040526
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Function of Xyloglucan Sidechain Substituents

Abstract: Xyloglucan (XyG) is a hemicellulose found in the cell walls of all land plants including early-divergent groups such as liverworts, hornworts and mosses. The basic structure of XyG, a xylosylated glucan, is similar in all of these plants but additional substituents can vary depending on plant family, tissue, and developmental stage. A comprehensive list of known XyG sidechain substituents is assembled including their occurrence within plant families, thereby providing insight into the evolutionary origin of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
124
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 108 publications
3
124
0
3
Order By: Relevance
“…The side chain substitution pattern of XyG can vary depending on the plant species (Schultink et al, 2014). However, recent analyses revealed that XyG structures can be tissue specific (Lampugnani et al, 2013;Dardelle et al, 2015;Liu et al, 2015).…”
Section: Hemicellulose Dynamics In the Primary Cell Wallmentioning
confidence: 99%
“…The side chain substitution pattern of XyG can vary depending on the plant species (Schultink et al, 2014). However, recent analyses revealed that XyG structures can be tissue specific (Lampugnani et al, 2013;Dardelle et al, 2015;Liu et al, 2015).…”
Section: Hemicellulose Dynamics In the Primary Cell Wallmentioning
confidence: 99%
“…galactopyranosyl, fucopyranosyl and arabinofuranosyl residues) according to plant tissue and species (Fig. 1) [10]. As a result of this structural complexity, complete XyG saccharification requires a consortium of endo-acting and exoacting glycoside hydrolases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The side-chain substitutions on XyG can be structurally diverse depending on plant species, tissue type, and developmental stage of the tissue (Pauly et al, 2001;Hoffman et al, 2005;Peña et al, 2008;Harris, 2009, 2012;Lampugnani et al, 2013;Schultink et al, 2014). A one-letter code nomenclature has been established to specify the XyG side-chain substitutions (Fry et al, 1993;Tuomivaara et al, 20145).…”
mentioning
confidence: 99%